House prices, rental costs, and mortgage interest rates - Lin, Che-Chun; Tsai, I-Chun (International Journal of Strategic Property Management, 2021)
Studies have typically adopted the price-rent ratio to determine whether housing exuberance exists and the periods of imbalance between house prices and rental costs. Using the price-rent ratio to conduct tests without considering the effects of mortgage interest rates on user costs may overestimate episodes of exuberance. This study uses data of the overall housing market and those of 10 major metropolitan statistical areas (MSAs) in the United States from 1979Q1 to 2018Q1 to evaluate whether housing exuberance exists in the markets; the results indicate that all the MSAs experienced episodes of exuberance at different times and the overall housing U.S. market was overheated from 1998Q2 to 2007Q3. By considering mortgage rates and using the user-cost-rent ratio, we further determine that short-term housing exuberance emerged in only two MSAs, Los Angeles and Miami, in 2006Q2, which was followed by immediate corrections. Thus, the research results of this study signify that only use the price-rent ratio to determine whether or not rational housing tenure choice made by traders exists is not sufficient. This study provides evidence showing that the method incorporating mortgage interest rates tends to obtain an equilibrium relationship between the rental and housing markets, indicating interest rates play an important role in housing tenure choice. First published online 31 May 2021